VISUALIZATION AND MEASUREMENT OF NATURAL CONVECTION BOUNDARY LAYER BY PARTICLE IMAGE VELOCIMETRY - Jha A.K.; Shukla P.; Ghosh P.; Khisti P.; Dubey A. (My University, 2025)
Natural convection boundary layer (NCBL) over a vertical flat plate has been widely studied because of its various scientific and real-life applications. Although the analytical solution of the velocity bound-ary-layer thickness is well-known, its experimental validation is presently limited. In this work, the visualization and measurement of a laminar NCBL formed over a heated vertical flat plate has been at-tempted by the particle image velocimetry (PIV) technique. This technique poses challenges when measurements are made near a solid wall where factors such as wall reflection and sharp velocity gradients are known to significantly influence the quality of PIV results. Special measures were taken to generate reliable near-wall data like removal of wall reflection, working with optimum particle image diameter. Experiments were performed on a vertical copper plate of length 150 mm, subjected to uniform heat fluxes of 500, 800, and 1500 W/m2. It was found that the boundary layer consists of a thin inner layer (~ 2 mm) and a thicker outer layer (~ 15 mm). The thicknesses of the inner and outer layers increase along the streamwise direction and decrease with the applied heat flux. The 2D steady, laminar natural convection boundary-layer equations at an experimental Prandtl number of 6.14 were solved to obtain the analytical solution. The experimental results are compared with the analytical solutions and it was found that both are in broad agreement. © 2023 by Begell House, Inc.